PREVALENCE AND PERSONAL FACTORS ASSOCIATED WITH SELF-HARM IN ADOLESCENTS - Kalyne Araújo Bezerra; Joyce de Sousa Lima; Gustavo de Oliveira Tavares; Vinicius Rodrigues de Oliveira; Soraya Maria de Medeiros; Jonas Sâmi Albuquerque de Oliveira (Universidade Federal do Paraná, 2023)
Objective: To identify the prevalence and personal factors associated with self-harm in adolescents. Method: A cross-sectional analytical observational study. The population consisted of notifications of interpersonal or self-harm violence in adolescents in Brazil from the Notifiable Diseases Information System. Notifications between 2009 and 2021 in Brazil were included in adolescents aged 10 to 19. The data was analyzed using descriptive and inferential statistics. Results: The prevalence of self-harm was 27.39% in Brazil. Black adolescents increase the prevalence of self-harm violence by 3% and brown and indigenous adolescents by 2%; more than eight years of schooling is a protective factor in relation to self-harm violence, reducing the prevalence of self-inflicted violence by 12%. Conclusion: The results indicate the need for effective policies and strategies to help care for this public.